The land before time III the time of the great giving - Bennett, Jeff.; Hogan, Heather; Smith, Roy Allen; MCA Universal Home Video (Universal City, Calif. : MCA Universal Home Video, 1995)
When a meteorite cuts off the water supply for the Great Valley, a young dinosaur named Littlefoot and his friends search for more water and find a large pool near the home of the dreaded Sharpteeth.
"82413"--Container.
Closed-captioned.
Director, Roy Allen Smith ; producers, Zahra Dowlatabadi, Roy Allen Smith ; animation producer, Nelson Shin ; screenplay, Dev Ross ; based on characters created by Judy Freudberg & Tony Geiss ; music, Michael Tavera ; original "Land before time" score by James Horner.
Voices: Jeff Bennett, Heather Hogan, Linda Grey, Nicholas Guest, Whitby Hertford, Candace Hutson, Kenneth Mars, Scott McAfee ; John Ingle, narrator.
VHS.
Keywords: Dinosaurs -- Juvenile films; Dinosaurs; Animated films; Films for the hearing impaired; Animated films; Children's films